Strabismus Surgery: A Retrospective Comparison of Different Postoperative Treatment Regimes to Prevent Infections - Felber, Daniel; Roulez, Francoise; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2022)
Background As studies have shown postsurgical polyvidone-iodine to be at least equal to postsurgical topical antibiotics, our postsurgical care regime was adjusted accordingly in 2017. Here, we retrospectively compared the postsurgical infection rate in patients who underwent strabismus surgery prior to and following this change in regimen in a routine clinical setting.Patients and Methods In this retrospective and explorative study, data from 162 adult patients who had undergone strabismus surgery was extracted from files: 98 patients who had received topical gentamycin in a combination ointment with steroid (postsurgery) followed by 1 week of topical gentamycin with nonsteroidal antiphlogistic eye drops for 1 week (group 1) and 64 who had received polyvidone-iodine once immediately postsurgically instead. We compared both groupsʼ postsurgical healing period regarding occurrence of bacterial conjunctival infection and conjunctival swelling and redness as well as other complications. Data were extracted from the entries of the routine follow-up dates on postsurgical days 1, 7, and at 3 months.Results Mean age of group 1 was 49 years and 51 years in group 2. There was no significant difference between the kind of surgeries (recessions/resections) or the number of patients who had undergone a reoperation. There was no significant difference between the groups for any of the endpoints analyzed at any of the three regular follow-up dates. From group 1, 12.04% and from of group 2, 6.25% showed bacterial conjunctivitis 1 week postsurgery. There was no endophthalmitis.Conclusion Topical polyvidone-iodine given once at the end of strabismus surgery is a good alternative to topical antibiotics with a comparable healing progress. It carries a comparable risk of infection as seen with a 1-week course of topical antibiotics. The advantages are less manipulation of the eye, no bacterial resistance caused, and cost efficiency. In addition, the lack of anti-inflammatories given in group 2 did not pose a disadvantage.
Keywords: gentamycin; strabismus surgery; polyvidone-iodine; antibiotic; antiphlogistic; postoperative